Planned organ preservation for elderly patients with rectal cancer using short course radiotherapy and a contact brachytherapy boost-an International multi-institution analysis. (March 2023) - Steinke, Jacqueline; Jordan, Chloe; Rossides, Savvas; Minnaar, Helen; Yu, Jimmy; Franklin, Adrian; Rockall, Tim; Dhadda, Amandeep Singh; Andrew Hunter, Iain; Mills, Jamie; Chadwick, Eliot; Silverman, Rafael; et al.
Highlights: Outcomes of 258 patients from 5 centres treated with SCRT and CXB are presented. Median follow up was 24 months and median age 81. 226 patients treated with radiotherapy alone had cCR of 78% with 16% local relapse (LR). 32 patients treated after local excision (LE) had cCR rate of 97% with 3% LR. 94% of patients remained stoma-free. Abstract: Background and purpose: The use of external beam radiotherapy (EBRT) and contact X-Ray brachytherapy (CXB) is emerging as an effective alternative in patients with early stage rectal cancer with the intent of organ preservation (OP). Short course radiotherapy (SCRT) is an alternative EBRT schedule for patients not fit for chemotherapy or for longer courses of EBRT. There are no multicentre studies that have reported on the outcomes of SCRT with a CXB boost, therefore we present these from patients from centres from the UK and Sweden. Materials and methods: From the Guildford Colorectal Database or local databases, 258 patients who underwent SCRT and CXB with the intent of OP from five centres treated between 2007 and 2019 were identified. Response and survival data was analysed and presented. Results: With a median age of 81, 226 patients were treated with radiotherapy alone (RTA) and 32 immediately after local excision (ILE). Median follow-up was 24 months. 70% and 97% of patients in the RTA and ILE groups respectively had a complete clinical response (cCR) after SCRT with CXB. Of those, local relapse was seen in 16% of the RTA and 3% of the ILE group. Median survival was 40 months after CXB in the RTA and 52 months in the ILE group. 94% of patients remained stoma-free to the point of latest follow-up. Conclusion: This data suggests that CXB when combined with SCRT, in a mainly elderly and comorbid population, provides good palliation with stoma-avoidance. Oncological outcomes compare with previously published work. A greater focus is required on quality of life outcomes after OP.